Performance of the new ID-fungi plate using two types of reference libraries (Bruker and MSI) to identify fungi with the Bruker MALDI Biotyper. (6th February 2020) - Heireman, Laura; Patteet, Sofie; Steyaert, Sophia
Abstract: During the last decade, matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) has revolutionized the diagnosis of fungal infections. Recently, a new Conidia ID-fungi plate (IDFP) medium was introduced to facilitate growth and sampling of fungi. This study aimed to evaluate the IDFP for fungal MALDI-TOF MS identification by comparison with a standard fungal growth medium using two reference libraries. A total of 75 filamentous fungal isolates (including 32 dermatophytes) were inoculated on IDFP and Sabouraud-gentamicin-chloramphenicol (SGC) agar and identified by MALDI-TOF MS using formic acid/acetonitrile extraction. Both the commercially available Bruker library (version 2.0) and the public available MSI web application (version 2018) were applied. For 15% of the isolates, a faster growth was noticed on IDFP compared to SGC. IDFP enhanced the performance of fungal identification compared to SGC for both MSI (increase of 16% identifications to genus and 5% to species level) and Bruker library (increase of 22% identifications to genus and 8% to species level). In total, only 73% of the tested isolates were present in the Bruker library compared to 92% for MSI library. No significant difference ( P  = 0.46) in MALDI score between IDFP and SGC was observed for the MSI library, but scores were significantly ( P  = 0.03) higher for IDFP when using Bruker library, potentially explained by the prevention of agar contamination by using IDFP since the Bruker database was created from liquid media. IDFP is a promising alternative growth medium for MALDI-TOF MS fungal identification which would strongly benefit from optimizing the Bruker reference library.